Corrosion and Quantum Studies of Alkyl Substituted Piperidin-4-Ones with Thiosemicarbazone on Mild Steel in an Acidic Medium - Shanmuga Priya, V.; Uma Rani, C.; Balachandran, V.; Velrani, S. (Journal of Science and Technology, 2018)
The acid corrosion inhibition technique of mild-steel in 1N sulfuric acid by a part of alkyl substituted 2,6-diphenyl piperidin-4-one with thiosemicarbazone has been observed by quantum chemical calculations, electrochemical AC impedance measurements, weight loss process and potentiodynamic polarization studies. Results show that substituted γ-2,c-6-diphenyl piperidin-4-ones with thiosemicarbazone act as perfect corrosion inhibitors and their inhibition efficiency increase with the addition of inhibitors. The potentiodynamic polarization curves pointed the studied inhibitors are mixed type of character and cathodic nature in 1 N H2SO4 media. The impedance spectroscopy shows a change in the value of charge transfer resistance (Rct) and double layer capacitance (Cdl) indicating the adsorption of the some substituted piperidin-4-ones with thiosemicarbazones on the mild steel surface. For all the three types of alkyl substituted 2,6-diphenyl pipieridin-4-one with thiosemicarbazone, the inhibition efficiency raised to increment in the inhibitor concentration and the performance of the three inhibitors are 01TS> 02TS> 03TS. The adsorption of the alkyl substituted 2,6-diphenyl piperidin-4-one with thiosemicarbazone on the mild-steel metallic surface pursued the Langmuir's adsorption isotherm. Quantum chemical calculations were executed by adopting density functional theory (DFT) to conclude whether a clear link exists among the inhibiting outcome of the inhibitor and the electronic characteristics of its main fundamentals.